2013
DOI: 10.1128/cvi.00719-12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid Device for Serological Diagnosis of Leishmania infantum Infection in Dogs as an Alternative to Immunofluorescence Assay and Western Blotting

Abstract: In this study, we compared a rapid immunochromatographic test (Speed Leish K; BVT Groupe Virbac, La Seyne sur Mer, France) with an indirect immunofluorescence assay (IFAT) and Western blotting (WB) for the detection of Leishmania infantum antibodies in dogs. A total of 250 serum samples were collected from 125 L. infantum-positive and 125 L. infantum-negative dogs. Among the positive samples, 81 were strongly positive at low IFAT dilutions, while 44 were low-reactivity sera (IFAT titers, 1:40 to 1:80). The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…Recently, an ICT kit claiming detection of antibodies developed after natural infection but not those elicited by vaccination with the LiESP‐based vaccine has been proposed as a tool to differentiate vaccinated from infected dogs . The principle of the test is sound, and a preliminary study reported a high sensitivity of this ICT format, while a further study reported a low sensitivity …”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, an ICT kit claiming detection of antibodies developed after natural infection but not those elicited by vaccination with the LiESP‐based vaccine has been proposed as a tool to differentiate vaccinated from infected dogs . The principle of the test is sound, and a preliminary study reported a high sensitivity of this ICT format, while a further study reported a low sensitivity …”
Section: Methodsmentioning
confidence: 94%
“…Recently, an ICT kit claiming detection of antibodies developed after natural infection but not those elicited by vaccination with the LiESP-based vaccine has been proposed as a tool to differentiate vaccinated from infected dogs. 128 The principle of the test is sound, and a preliminary study reported a high sensitivity of this ICT format 129 , while a further study reported a low sensitivity. 130 The IFAT is considered the reference method for anti-Leishmania serology in dogs [126][127][128][129][130][131] based on the high sensitivity and specificity (near 100% for both) except in areas endemic for the New World parasite Trypanosoma cruzi that may give false-positive results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the reaction between Leishmania antigens and antibodies was performed using the indirect enzymelinked immunosorbent assay (ELISA), which is extensively used in diagnostic laboratories or clinical testing. 68 This technique is the preferred method to determine purified antibodies and can also be successfully employed for the qualitative and quantitative assessment of an antigen in a sample. 68,69 After the completion of the procedures detailed in the methods section, the results are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…For the diagnosis of CVL and human VL, among the tested and commercially available recombinant proteins, the most widely used for composing immunochromatographic tests is the recombinant protein rK39. This protein contains repetitive sequences of 39 amino acids from a protein related to kinesin of kinetoplast from L. infantum, and has been widely used in ELISA platform as described above [30,31,91,96,97,110,[113][114][115][116][117][118][119].The efficacy of rK39-based rapid lateral flow test was compared with the IFAT against sera of parasitologically positive dogs from Italy. Both tests offered similar sensitivities of 97% for the lateral flow test in the dipstick format and 99% for the DAT, as well as the maximum specificity of 100% in both tests [120].…”
Section: • Rapid Testsmentioning
confidence: 99%